1996
DOI: 10.1046/j.1365-2133.1996.d01-1030.x
|View full text |Cite
|
Sign up to set email alerts
|

Brachioradial photopruritus-a rare chronic photodermatosis in Europe

Abstract: Brachioradial pruritus (BRP) is an uncommon localized pruritic dermatosis only previously described from the tropics and subtropics. We report two cases in British residents who had a history of prolonged ultraviolet radiation exposure, and who responded to strict photoprotection of the affected sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
1
2
0
3
Order By: Relevance
“…[1][2][3] For nearly 30 years, BRP was considered to be related to ultraviolet (UV) irradiation because UV exposure worsens the symptom. 2,[4][5][6][7][8][9][10][11][12][13][14] As early as 1983, Heyl 3 proposed that BRP may be caused by nerve injury in the cervical spine or by nerve compression (NC). Several recent studies have suggested that BRP may result from cervical spine lesions such as radiculopathy, disk herniation, osteophytes, or spinal neoplasms.…”
mentioning
confidence: 99%
“…[1][2][3] For nearly 30 years, BRP was considered to be related to ultraviolet (UV) irradiation because UV exposure worsens the symptom. 2,[4][5][6][7][8][9][10][11][12][13][14] As early as 1983, Heyl 3 proposed that BRP may be caused by nerve injury in the cervical spine or by nerve compression (NC). Several recent studies have suggested that BRP may result from cervical spine lesions such as radiculopathy, disk herniation, osteophytes, or spinal neoplasms.…”
mentioning
confidence: 99%
“…Die Patienten geben häufig nicht ein reines Jucken an, sondern vielmehr auch eine brennende oder schmerzende Komponente [5,12,18]. Bei chronischem brachioradialen Pruritus entwickeln sich nicht selten durch das chronische Kratzen Lichenifikationen, Prurigo simplex oder Prurigo nodularis [20,18].…”
Section: Tab 1 Brachioradialer Pruritusunclassified
“…Es wurden verschiedene Ursachen diskutiert, u. a. eine chronische UV-Exposition der Haut. Gepaart mit der Beobachtung eines saisonalen Auftretens des Pruritus zwischen Juli und November [20] führte dies anfänglich zu dem Namen "solarer Pruritus" oder "recurrent solar dermopathy [20,12]. In diesem Zusammenhang wurden immer wieder Patienten beschrieben, die in den Tropen oder Subtropen leben oder viele Outdoor-Freizeitaktivitäten wahrnehmen [20,10,19].…”
Section: Tab 1 Brachioradialer Pruritusunclassified
See 1 more Smart Citation
“…Although this condition was initially described in 1968 by Waisman, the exact cause of BRP is still debated due to a paucity of data on patients with this uncommon form of localized itching. The two most common theories include extensive solar ultraviolet radiation and cervical spine disease …”
mentioning
confidence: 99%